2018
DOI: 10.1021/acs.energyfuels.8b03550
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Removal Efficiency of Low-Partial-Pressure H2S in a Monoethanolamine-Activated N-Methyldiethanolamine Aqueous Solution

Abstract: The absorption performance of low-partial-pressure H 2 S in a monoethanolamine (MEA)-activated Nmethyldiethanolamine (MDEA) aqueous solution was investigated. The absorption amount (in mass, g H 2 S/g solutions) and H 2 S loadings (mol H 2 S/(mol MEA + mol MDEA)) were measured, and the apparent absorption rate was determined from the time-dependent absorption capacity. Experimentally, the temperature and partial pressure of H 2 S (P H 2 S ) ranged from 303.2 to 323.2 K and from 300 to 500 Pa, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…For 3DEA-1P and DEAE-EO a higher reduction in the absorption capacity is seen. Overall, the results indicate that increase in amine concentration changes the vapor-liquid equilibria behavior of the system [16,27,41,42].…”
Section: Effect Of Amine Concentrationmentioning
confidence: 78%
See 2 more Smart Citations
“…For 3DEA-1P and DEAE-EO a higher reduction in the absorption capacity is seen. Overall, the results indicate that increase in amine concentration changes the vapor-liquid equilibria behavior of the system [16,27,41,42].…”
Section: Effect Of Amine Concentrationmentioning
confidence: 78%
“…For 3DEA-1P and DEAE-EO a higher reduction in the absorption capacity is seen. Overall, the results indicate that increase in amine concentration changes the vapor-liquid equilibria behavior of the system [16,27,41,42]. The data at 50 wt% allows us to compare the absorption capacity of 3DEA-1P, DEAE-EO and DBEA in aqueous and MEG solutions with similar mole fraction (mole amine/mole solution).…”
Section: Effect Of Amine Concentrationmentioning
confidence: 83%
See 1 more Smart Citation
“…Many studies have shown that a mixed alkanolamine solution has better desulfurization performance than a single alkanolamine solution [ 9 , 10 , 11 ]. Our previous study indicated that adding small quantities of MEA to MDEA aqueous solutions can obviously improve the H 2 S absorption capacity and absorption rate [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we used MDEA aqueous solutions promoted by two ILs, namely tetramethylammonium glycinate ([N 1111 ][Gly]) and tetramethylammonium arginate ([N 1111 ][Arg]), to explore the performances of such mixed solutions for absorbing H 2 S. The results showed that the two AAILs were superior to MEA in promoting the absorption of H 2 S by MDEA solution. Moreover, of these two promoters, the MDEA aqueous solutions promoted by [N 1111 ][Arg] exhibited the highest absorption capacity and absorption rate for low-concentration H 2 S. Therefore, [N 1111 ][Arg]-promoted MDEA aqueous solutions show commercial potential [ 12 , 25 ].…”
Section: Introductionmentioning
confidence: 99%